Warriors : Tigerstar & Sasha - Hunter, Erin; Hunter, Erin; Jolley, Dan (Hunter, Erin. Warriors (Graphic novel), 2025)
"When Sasha is forced to leave her kittypet home, she must forge a solitary new life in the forest. Then she meets Tigerstar, leader of the ShadowClan, and wonders whether she would be btter off joining the ranks of his forest Clan. But Tigerstar has many secrets, and Sasha isn't sure she can trust him. Will she wander alone forever? And where does she belong? This volume includes all three books in the Tigerstar and Sasha trilogy--now in full color for the first time!"--Back cover.